Benign tumors in gynecology and obstetrics. Benign ovarian tumors, histogenesis and classification. - Novoa Vílchez, Salomón (2015)
The author makes an embryological count of female gonad to orientate in a histological classification of benign ovarian tumors. The difficulty referred to in order histological benign tumors because they are malignant or benign indifferently. Finally sequence is reviewed in the histogenesis of each of the mentioned tumors.